Modern treatment of epileptic encephalopathies in young children: improvement of precision medicine - L.G. Kirilova; O.O. Miroshnikov; O.E. Abaturov; N.V. Medvedovska; Yu.G. Antipkin; N.Y. Bondarenko (Zaslavsky O.Yu., 2023)
Background. Treatment of epileptic seizures in young children, especially with epileptic encephalopathies (EE), is a difficult task, which is impossible in modern conditions without the use of a personified (precision) therapy. The diagnostic algorithm for EE must include genetic examination by the next-generation sequencing, which makes it possible to prescribe targeted therapy depending on the genetic etiology of the disorder. The article presents the results of own research on the effectiveness and approaches to targeted therapy of genetic epileptic encephalopathies in young children. Materials and methods. Fifty-eight children aged 0-3 years with clinical manifestations of epileptic encephalopathies, onset of seizures in the first year of life and diagnosed genetic etiology were included in the study. Pathogenic variants in genes associated with the development of epileptic seizures were identified in all children using the next-generation sequencing. The study included assessment of neurological status, history collection, evaluation of semiology and seizure type, development and screening for autism spectrum disorders at the age of 18 and 24 months, video-electroencephalography during night sleep, magnetic resonance imaging of the brain, assessment of antiepileptic treatment received by the child. Results. Of 58 children with EE who were prescribed antiepileptic drugs, 10 (17.2 %) received monotherapy, 40 patients (69 %) received combined therapy with two anticonvulsants, and 8 children (13.8 %) - combined therapy with three or more anticonvulsants. Levetiracetam (31 patients), valproic acid salt preparations (20 cases), topiramate (11 children) and vigabatrin (10 cases) were most used antiepileptic drugs. In all examined patients with EE, we used schemes of targeted (personalized) antiepileptic therapy focused on the genetic etiology of the disorder. In children with tuberous sclerosis caused by mutations in the TSC1 and TSC2 genes, vigabatrin (50-150 mg/kg per day) was included in the antiepileptic therapy and showed efficacy in 75.0 % (9/12) of children with infantile spasms. Corticosteroids (adrenocorticotropic hormone or prednisone) were additionally included in the treatment regimen and showed effectiveness in 66.7 % of cases (4/6). In children with mutations in SCN1A gene, combined therapy including valproic acid, topiramate and clobazam, or valproic acid with levetiracetam and corticosteroids was used, which showed effectiveness in reducing the frequency of seizures in 100 % of cases. Conclusions. Epileptic encephalopathies are a heterogeneous group of genetic disorders in young children that are difficult to treat and often have a malignant course. Since standard antiepileptic drugs are often insufficiently effective in epileptic encephalopathies, the use of targeted therapy drugs and alternative treatments such as hormone therapy are extremely important. The goal of treatment for epileptic encephalopathies is not only to control seizures, but also to prevent the development of neurological and cognitive deficits and restore lost functions.